RF circuit design - Bowick, Chris (Newnes/Elsevier, 2008)
Its Back! New chapters, examples, and insights; all infused with the timeless concepts and theories that have helped RF engineers for the past 25 years! RF circuit design is now more important than ever as we find ourselves in an increasingly wireless world. Radio is the backbone of todays wireless industry with protocols such as Bluetooth, Wi-Fi, WiMax, and ZigBee. Most, if not all, mobile devices have an RF component and this book tells the reader how to design and integrate that component in a very practical fashion. This book has been updated to include today's integrated circuit (IC) and system-level design issues as well as keeping its classic "wire lead" material. Design Concepts and Tools Include The Basics: Wires, Resistors, Capacitors, Inductors Resonant Circuits: Resonance, Insertion Loss Filter Design: High-pass, Bandpass, Band-rejection Impedance Matching: The L Network, Smith Charts, Software Design Tools Transistors: Materials, Y Parameters, S Parameters Small Signal RF Amplifier: Transistor Biasing, Y Parameters, S Parameters RF Power Amplifiers: Automatic Shutdown Circuitry, Broadband Transformers, Practical Winding Hints RF Front-End: Architectures, Software-Defined Radios, ADCs Effects RF Design Tools: Languages, Flow, Modeling Check out this books companion Web site at: http://books.elsevier.com/9780750685184 for full-color Smith Charts and extra content! *Completely updated but still contains its classic timeless information *Two NEW chapters on RF Front-End Design and RF Design Tools *Not overly math intensive, perfect for the working RF and digital professional that need to build analog-RF-Wireless circuits.
Keywords: Radio circuits -- Design and construction.; Radio frequency.; elektronické knihy; electronic books